Actual Issues of the History of Islamic Sects - Ahmetoghlu, Shahin (Scholarya Demo Journal of Ruby, 2019)
History of Islamic Sects has passed through many stages from the beginning to the present, and each sect formed its own written literature in the process, and many works have been written about the sects. Many of these works have survived to the present day, however, it is known that there aremany works that were lost. Based on the available sources it is possible to say that the area has a rich accumulation. History of Islamic Sects now has animportant place among scientific disciplines with its unique features. Obtainin greliable data in scientific research, identifying problematic issues, careful and objective determination of metrics lead to the achievements in the scientific researches. The originality of the works that make an important contribution to science helps the solution of today’s problems highlighting the past. On the other hand, the history of Islamic Sects, which continue to be up-to-date, is taught both in the relevant faculties of the universities and also in the curricula of other educational institutions. Each scientific discipline has its application methods and forms. There are also methods used by the History of Islamic Sects in this sense. In our article, the definition of Islamic sects, the concepts related to the field will be clarified, the sources of the field and the traditions of writing will be mentioned, however, the current issues related to the sects, some important methodological methods will be given.